2020
DOI: 10.1155/2020/5084062
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Levels of Heavy Metals and Formaldehyde in Baby Clothes in South Africa: A Case Study of Stores in the Greater Cape Town Region

Abstract: Herein, we report on the determination of formaldehyde, pH, and heavy metals (Pb, As, Co, Cr, Ni, and Cd) in various baby apparel (cotton, polyester, nylon, elastane, and polyethylene) of different colours (light, medium, and dark) purchased from both high-end and low-end market stores. The concentrations of the heavy metals were determined by inductively coupled plasma (ICP) after wet digestion and also after extraction using artificial sweat for a selected range of skin-contact baby apparel. The relative sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…These levels were similar to those found by Aldag et al [ 23 ], who reported a maximum level 75.9 mg/kg in several T-shirts and pants purchased in Germany. By contrast, formaldehyde levels in 34 textile samples acquired in South Africa were found within the range 0.036–0.090 mg/kg [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…These levels were similar to those found by Aldag et al [ 23 ], who reported a maximum level 75.9 mg/kg in several T-shirts and pants purchased in Germany. By contrast, formaldehyde levels in 34 textile samples acquired in South Africa were found within the range 0.036–0.090 mg/kg [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heavy metal concentrations in the samples investigated could be used to predict skin toxicity and estimate human exposure and health hazards. When metals are present in textile materials above specified levels, they may present a risk to human health through absorption through the skin [ 25 ]. The amounts of heavy metals in the T-shirts under investigation differed from one color to the other.…”
Section: Discussionmentioning
confidence: 99%
“…The pH was determined using a modified version of the method developed by the International Organization for Standardization (ISO 3071:2005), as reported by Nyamukamba et al [14]. About 2.0 g of the diapers were cut into small pieces for effective wetting of the samples and put in a volumetric flask containing 100 mL of water (pH 7.0, 27 • C).…”
Section: Ph Determinationmentioning
confidence: 99%
“…It is very important for formaldehyde to be within the limits for the safety of the babies, since formaldehyde can cause skin irritation and skin allergies and is carcinogenic to humans [20,21]. It has also been found that formaldehyde causes irritation of the mucous membrane and upper respiratory tract, as well as ocular irritation, among others [14,22]. When children are exposed to chemicals at an early stage, it can have serious and long-lasting implications.…”
Section: Formaldehydementioning
confidence: 99%